Mesoscopic multiterminal Josephson structures. I. Effects of nonlocal weak coupling - Amin, M. H. S.; Omelyanchouk, A. N.; Zagoskin, A. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We investigate nonlocal coherent transport in ballistic four-terminal Josephson structures (in which bulk superconductors (terminals) are connected through a clean normal layer, e.g., a two-dimensional electron gas). Coherent anisotropic superposition of macroscopic wave functions of the superconductorsin the normal region produces phase slip lines (2D analogs to phase slip centers) and time-reversal symmetry breaking 2D vortex states in it, as well as such effects as phase dragging and magnetic fluxtransfer. The tunneling density of local Andreev states in the normal layer is shown to contain peaks at the positions controlled by the phase differences between the terminals. We have obtain the general dependence of these effects on the controlling supercurrent/phase differences between the terminals of the ballistic mesoscopic four-terminal SQUID.